2014
DOI: 10.1016/j.cageo.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional numerical simulations on wind- and tide-induced currents: The case of Augusta Harbour (Italy)

Abstract: a b s t r a c tThe hydrodynamic circulation in the coastal area of the Augusta Bay (Italy), located in the eastern part of Sicily, is analysed. Due to the heavy contamination generated by the several chemical and petrochemical industries active in the zone, the harbour was declared a Contaminated Site of National Interest. To mitigate the risks connected with the industrial activities located near the harbour, it is important to analyse the hydrodynamic circulation in the coastal area. To perform such analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 29 publications
4
12
0
Order By: Relevance
“…On the other hand, the wind had a much higher impact on the velocities-up to more than one order of magnitude. This is in agreement with De Marchis et al [15] and Fenocchi et al [13], who as well observed an increase of flow velocities of one order of magnitude in the case of wind and especially during storm events. For the density-induced flow, a velocity increase took place to a lower extend in some specific zones, e.g., on the bottom and superficial layers next to the lateral boundaries, while there was a general decrease at the intermediate water depths.…”
Section: Synthesis and Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…On the other hand, the wind had a much higher impact on the velocities-up to more than one order of magnitude. This is in agreement with De Marchis et al [15] and Fenocchi et al [13], who as well observed an increase of flow velocities of one order of magnitude in the case of wind and especially during storm events. For the density-induced flow, a velocity increase took place to a lower extend in some specific zones, e.g., on the bottom and superficial layers next to the lateral boundaries, while there was a general decrease at the intermediate water depths.…”
Section: Synthesis and Discussionsupporting
confidence: 93%
“…The results of the WIND and the HEAT scenarios, compared with the reference REF, showed that strong wind and density changes had an impact on the flow field, confirming a wide range of previous studies (e.g., [6,12,13,15,19]). On the one hand, while the configuration of the flow following the SE wind was maintained over time both horizontally and vertically, the imposed constant ∆T equal to 10 • C changed it substantially (e.g., the flow in the surface layers was induced from the shallow to the deeper waters).…”
Section: Synthesis and Discussionsupporting
confidence: 85%
See 3 more Smart Citations